2019
DOI: 10.5547/01956574.40.si1.gbje
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Combination of Taxes on Fuel and Vehicles

Abstract: A tax on fuel combined with tax exemptions or subsidies for fuel-efficient vehicles is implemented in many countries to reduce greenhouse gas emissions and other negative externalities from road traffic. This study, however, shows that a tax on fuel should be combined with heavier taxation of fuel-efficient vehicles to curb externalities from road traffic. The tax on fuel is implemented in order to curb externalities linked to both consumption of fuel and road use. A heavier tax on fuel-efficient vehicles prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Indeed, there is renewed academic interest in alternative road pricing mechanisms, such as congestion or GPS-based charging, cordon pricing, optimal toll pricing, real time road pricing, or "superblocks" of pedestrian-only traffic (see Parry et al, 2007;Guo et al, 2017;Cramton et al, 2018;Bjertnaes, 2019;Mueller et al, 2019). However, ideal externality-correcting mechanisms have not been widely implemented and most plans to introduce congestion charging are advancing slowly (Reid, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is renewed academic interest in alternative road pricing mechanisms, such as congestion or GPS-based charging, cordon pricing, optimal toll pricing, real time road pricing, or "superblocks" of pedestrian-only traffic (see Parry et al, 2007;Guo et al, 2017;Cramton et al, 2018;Bjertnaes, 2019;Mueller et al, 2019). However, ideal externality-correcting mechanisms have not been widely implemented and most plans to introduce congestion charging are advancing slowly (Reid, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…31 Still, the benefit of the fuel tax over a congestion charge is that a fuel tax can, at least indirectly, address all large externalities caused by driving concurrently, and be used to generate a broader revenue base for the government (Rietveld and van Woudenberg, 2005). It also encourages improvements in the fuel economy of the fleet by encouraging the purchase of more efficient new cars, and in some cases, more fuel efficient driving patterns (Dhondt et al, 2013;Bjertnaes, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the current tax difference between fuel and non-polluting goods amounts to approximately 28 cents per gallon of gasoline in the US. The average toll per gallon of gasoline amounts to approximately 9 cents according to Bjertnaes (2017). The current US tax difference between fuel and non-polluting goods, including fees for toll roads, equals 0.37 dollar per gallon of gasoline.…”
Section: Fuelmentioning
confidence: 99%
“…The additional value-added tax is levied on most goods including fuel, and thus does not influence the tax difference. Toll per gallon of gasoline on roads and bridges in the UK is marginal according to Bjertnaes (2017).…”
Section: Fuelmentioning
confidence: 99%
“…An alternative to this was suggested by Parry (2012), who proposed a tax based on the distance driven, to be measured by a GPS device installed in each vehicle. Bjertnaes (2017), assuming rational behaviour by consumers, described a utility function developed for a fuel tax that would correct externalities according to fuel consumption and road use. Other analysts have observed that, in addition to fuel, vehicle emissions may be influenced by lifestyle and sociocultural factors (Brand, 2019).…”
Section: Introductionmentioning
confidence: 99%